The use of alternative energy sources in the Zaporozhye region - Bondarenko, V.; Donenko, V.; Shcherbyna, L. (Ways to Improve Construction Efficiency, 2019)
This article explores the use of alternative energy sources in the Zaporozhye region. The most common types of alternative energy sources for the eastern regions of Ukraine are described, the feasibility of their use, advantages and problems of their introduction. Also, examples of existing power generating stations of Zaporizhzhya region are given, real prices of realization of projects on their construction and start-up are given.